Pelaksanaan Remisi Terhadap Warga Binaan Di Rumah Tahanan Klas II B Magetan - Juanita, Septika Rindu, Dr. Natangsa Surbakti, S.H., M.Hum (2017)
This study aims to determine how the implementation of remission and constraints and solutions in the implementation of remission to inmates at the Detention Class II B Magetan. Remission is a reduction in criminal past were given to prisoners and criminal children who have behaved well during a sentence except those sentenced to death or life imprisonment. This study outlines the guidance system for inmates serving sentences. Coaching is an activity that is continued and intensified in order to convict realizing his mistake, to improve themselves and not committing a crime again. In other words, prisoners should be recognized as a basic human rights for human and obtaining justice. If the inmate or inmates behave well then it can be considered in granting remission. But in granting remission is certainly not without difficulties, resulting in this study also outlines about what are the obstacles in remissions and how solutions at their disposal. Keyword :Remission, Convict, Development